The Effect of Lavender Aromatherapy on Reducing the Intensity of Labor Pain in the 1st Active Phase - Laska, Yulinda; Husna, Ridni; Siregar, Masdalena; Hariyati, Shapna Lina (JURNAL KEBIDANAN, 2023)
Labor is a physiological process, labor pain causes worry, panic, depression and delays the progress of the labor process. Labor pain can be reduced using pharmacological and non-pharmacological methods. One nonpharmacological method is to use aromatherapy. This study aims to determine the effect of the use of lavender aromatherapy on reducing the intensity of labor pain in the active phase of the first stage of labor. Methods: This was a quasy experimental study with a one group pretest-posttest without control approach. The population in this study involved all women in labor in March 2023 at the Private Practice Midwives in the work area of Puskesmas Botania CHC, Batam City, Riau Island. The number of samples was 30 women who were selected with the Total Sampling technique. The instrument used was the NRS pain scale observation sheet, and use defuser with lavender essensial oil 4 drop in 300 waters. Data analysis applied the Wilcoxon test. Results: The results showed that the mean scores of intensity of labor pain in the active phase of the first stage of labor before and after lavender aromatherapy administration were 5,83 and 4,97, respectively. The result of the analysis obtained a p-value of 0.000 (p<0.05). Conclusion: There is an effect of lavender aromatherapy on pain intensity in phase I active labor.